2007
DOI: 10.1177/1090198107309456
|View full text |Cite
|
Sign up to set email alerts
|

Focus Groups of Alaska Native Adolescent Tobacco Users: Preferences for Tobacco Cessation Interventions and Barriers to Participation

Abstract: Tobacco cessation interventions developed for Alaska Native adolescents do not exist. This study employed focus group methodology to explore preferences for tobacco cessation interventions and barriers to participation among 49 Alaska Natives (61% female) with a mean age of 14.6 (SD = 1.6) who resided in western Alaska. Using content analysis, themes from the 12 focus groups were found to be consistent across village, gender, and age groups. Program location or site (e.g., away from the village, hunting, fishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…Previous exploratory studies conducted in western Alaska reported that, although tobacco has no ceremonial use, iqmik is considered a “natural” product and, thus, its use is considered a healthier practice than cigarette smoking. Hence, iqmik use is culturally acceptable for women to use during pregnancy and, in some communities, for young children to assist in its production with pre-mastication prior to storage and later adult consumption [37,38]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous exploratory studies conducted in western Alaska reported that, although tobacco has no ceremonial use, iqmik is considered a “natural” product and, thus, its use is considered a healthier practice than cigarette smoking. Hence, iqmik use is culturally acceptable for women to use during pregnancy and, in some communities, for young children to assist in its production with pre-mastication prior to storage and later adult consumption [37,38]. …”
Section: Methodsmentioning
confidence: 99%
“…A small sample size was reported as a limitation by three studies (Dworkin, Larson, & Hansen, 2003;Hoppe et al, 2004;Patten et al, 2007). The willingness to participate in a study because of the teens' relationship with a provider or health care agency (Carroll et al, 2007) and confidentiality concerns (Molock et al, 2007) were also identified as limitations.…”
Section: Recruitmentmentioning
confidence: 97%
“…American Indian/ Alaska Native 8 34 , qualitative Focus groups showed that Alaska Native adolescent tobacco users reported that they preferred cessation interventions that included location that were accessible to them, a group-based format, inclusion of medication, and personal stories. Motivators to quit included adverse health effects, improved self-image and appearance, and being a future role model.…”
Section: Domain 1: Understanding Tobacco Use and Related Diseasesmentioning
confidence: 99%
“…Alaska Native adolescent tobacco users reported preferences for interventions tailored to their group. 34 Social and community networks also facilitated the conduct of research in the community: one pilot found in-person contact was more cost-effective than media to recruit for a tobacco survey, 43 and highly mobile Spanish-speaking immigrant smokers were able to participate in intensive assessments and receive tobacco cessation assistance. 44 Community-specific beliefs impeding or facilitating cessation are distinct and varied.…”
Section: Psychosocial Researchmentioning
confidence: 99%